Pengaruh Customer Engagement terhadap Online Purchase Intention dengan Customer Operant Resources Sebagai Variabel Intervening pada Layanan Platinum Mahasiswa di Vidio.com - Ratnawati, Lela Septatiana; Sanaji, Sanaji (Universitas Proklamasi 45, 2024)
This study aims to analyze the impact of Customer Engagement on Customer Operant Resources and Online Purchase Intention among Vidio.com users who are university students in Indonesia. The research sample comprises 280 respondents aged 18-23 years who have accessed free content on Vidio.com in the past six months. Data were collected through adapted questionnaires, and their validity and reliability were tested. The analysis results show that Customer Engagement has a significant effect on Customer Operant Resources, indicating that customer engagement positively influences operant resources. Additionally, Customer Engagement also significantly affects Online Purchase Intention, indicating that customer engagement increases online purchase intention. However, the interaction between Customer Operant Resources and Customer Engagement does not have a significant effect on Online Purchase Intention. This study contributes theoretically by enriching the literature on the role of Customer Engagement and Customer Operant Resources in the context of subscription to Vidio.com. Practical implications for Vidio.com management include strategies to increase engagement through attractive and interactive content to boost users' purchase intentions. Suggestions for future researchers include expanding the sample size and examining additional variables that might affect online purchase intentions. This study also provides insights for fellow users on the importance of active engagement on the platform to achieve a better experience.